2012
DOI: 10.1186/cc11323
|View full text |Cite
|
Sign up to set email alerts
|

Acetazolamide: a second wind for a respiratory stimulant in the intensive care unit?

Abstract: Patients with chronic obstructive pulmonary disease (COPD) are affected by episodes of respiratory exacerbations, some of which can be severe and may necessitate respiratory support. Prolonged invasive mechanical ventilation is associated with increased mortality rates. Persistent failure to discontinue invasive mechanical ventilation is a major issue in patients with COPD. Pure or mixed metabolic alkalosis is a common finding in the intensive care unit (ICU) and is associated with a worse outcome. In patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Bicarbonate on the other hand is found to remain elevated in patients with posthypercapnic alkalosis (Banga and Khilnani, 2009). It is suggested that excreting bicarbonate could correct metabolic alkalosis and, subsequently, increase minute ventilation and improve oxygenation, facilitating weaning from mechanical ventilation in patients with COPD or other pulmonary diseases (Heming et al, 2012). Recently, Faisy et al showed in a randomized trial that the use of acetazolamide did not result in a significant reduction in the duration of mechanical ventilation compared to placebo (Faisy et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Bicarbonate on the other hand is found to remain elevated in patients with posthypercapnic alkalosis (Banga and Khilnani, 2009). It is suggested that excreting bicarbonate could correct metabolic alkalosis and, subsequently, increase minute ventilation and improve oxygenation, facilitating weaning from mechanical ventilation in patients with COPD or other pulmonary diseases (Heming et al, 2012). Recently, Faisy et al showed in a randomized trial that the use of acetazolamide did not result in a significant reduction in the duration of mechanical ventilation compared to placebo (Faisy et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…2 The authors did not report on changes in daily fluid balance and urine output. Although the net diuretic effect is usually modest (sodium reabsorption in more distal nephron segments may offset proximal sodium losses), its quantification might have helped better understand the results of this trial.…”
Section: Acetazolamide and Invasive Mechanical Ventilation For Patienmentioning
confidence: 99%
“…2 Second, if the role of acetazolamide, according to the authors, is to assist in weaning, then what was the rationale for starting it at the initiation of mechanical ventilation? It could be considered at the time of initiation of the weaning process.…”
Section: Acetazolamide and Invasive Mechanical Ventilation For Patienmentioning
confidence: 99%
See 1 more Smart Citation
“…ACTZ is a carbonic anhydrase inhibitor that is in clinical use for treatment of a variety of medical conditions, including as a respiratory stimulant in patients with COPD and metabolic alkalosis (59). Treatment from the outset of bacterial infection, as in our study, is somewhat artificial, but in future work we will investigate the therapeutic potential of this drug by treatment of infected mice at later time points of infection and by different routes of administration, since systemic inhibition of pendrin activity may lead to unwanted deleterious effects on other organs.…”
Section: Discussionmentioning
confidence: 99%